PSXVII-15 Evaluation of online modules designed for youth to learn about biosecurity. (7th December 2018) - Smith, J; McDonald, J; Kerr, S; Rankin, J; Sero, R
Abstract: Formative and summative evaluation are core elements of program development. We will demonstrate and discuss the formative evaluation of a set of highly interactive online modules on the topic of biosecurity. As part of a larger multi-state USDA NIFA Coordinated Agricultural Project, a national education team of three subject matter experts, led by a distance education expert, created a series of four modules designed for youth audiences between 6 th and 12 th grade. The modules are titled: (1) What is Biosecurity? (2) Routes of Infection and Means of Transmission, (3) Finding Sources of Disease Transmission Risk, and (4) Biosecurity Strategies. Because they build on each other, opportunities to review foundational concepts and to link to additional information are provided in more advanced modules, but any module can be accessed independently. We incorporated a thorough process of review into the development and deployment of the modules. Nationwide peer-reviewers, selected based on their subject-matter expertise and hands-on experience of working with youth livestock projects, were asked to evaluate the modules on multiple aspects of five dimensions: content, interactivity, effectiveness, usability, and versatility. These reviews led us to increase the low-end of the age range for the target audience from 3 rd to 6 th grade. The revised modules were then piloted by 4-H and FFA youth and adult leaders. The pilot evaluators were asked about a number of concepts including content, effectiveness, and recommendations for improvement. This feedback was used to finalize the modules. All evaluation procedures have the approval of the Institutional Review Board at Washington State University. Funding for this effort is partially supported by the National Institute of Food and Agriculture, U.S. Department of Agriculture, under award number 2015-69004-23273.